Generalized Meningococcal Disease in the Newborn: Clinical Case and Literature Review - Irina Ya. Izvekova (Педиатрическая фармакология)
Neisseria meningitidis is one of the main etiological factors of meningitis and sepsis in children and adults, however, it is rarely diagnosed in the neonatal period. Clinical definition of neonatal meningococcal disease is complicated, the disease outcome is commonly lethal, and therefore its timely diagnosis and adequate therapy are crucial. This article describes clinical case of the newborn with meningococcal sepsis hospitalized on the 5th day after birth and provides the literature review of the data from the late 19th century until the present.